Tinjauan Filosofis tentang Kebutuhan dan Tanggung Jawab Peserta Didik - Syafi'i, Imam (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2019)
In education, learners are individuals who have potential to develop. In the development of learners, intrinsically essentially have needs that must be met and responsibilities that must be carried out. that must be carried out. This literature research seeks to analyze the fulfillment of the needs and responsibilities of students which is an important instrument for their character development. The findings of this research reveal that students have diverse potentials that need to be developed by teachers through the education process. education process. The needs of learners that must be met include among others: physical needs, social needs, the need to get status, independent needs, achievement needs, love needs. status, need to be independent, need to achieve, need for love, need to provide input to each other, and need for support. affection, the need to provide mutual input, and the need for religion. religious needs. While the responsibilities of learners are as follows as follows: First, they must purify their souls from impurities and disease of the soul. Second, always concentrate on the knowledge that is being Second, always concentrate on the knowledge he is learning and reduce worldly preoccupations. Third, studying Third, study knowledge gradually with patience and fortitude. Fourth, knowing the value of the knowledge he learns. Fifth, always always try to get the pleasure of the teacher and always respect the teacher. respect his teacher. Fulfillment of needs and responsibilities fulfillment of the needs and responsibilities of students is part of the process of students to have noble morals. have noble morals. Noble morals are the main capital to seek knowledge and achieve success